Association between lactate-to-albumin ratio and short- and long-term mortality in critically ill patients with ischemic stroke: a retrospective analysis of the MIMIC-IV database: Lactate-to-Albumin Ratio and Mortality in Ischemic Stroke - Qin, Sisi; Xiao, Jijie; Yuan, Shiqi; Zhang, Huitao; Liu, Yang; Li, Ningjun; He, Songjin; Kou, Li (Journal of Medical Biochemistry, 2025)
Background: Stroke is a major cause of disability and cognitive deficits, with ischemic stroke (IS) being the most prevalent type, especially in critically ill patients in intensive care units (ICUs). The lactate-to-albumin ratio (LAR) has emerged as a potential predictor of disease outcomes, but its association with short- and long-term mortality in critically ill IS patients is unclear.Methods: This study analyzed data from 894 critically ill IS patients from the MIMIC-IV database, categorized into LAR tertiles. Clinical endpoints included ICU, hospital, and 30- and 90-day all-cause mortality. Survival differences were assessed using Kaplan-Meier analysis. Cox proportional-hazards regression models and restricted cubic spline (RCS) analysis evaluated the association between LAR and mortality outcomes. Subgroup analyses examined the modifying effects of clinical characteristics on LAR’s predictive value.Results: The ICU, hospital, 30-, and 90-day mortality rates were 15.0%, 22.3%, 28.2%, and 36.1%, respectively. Higher LAR levels were associated with reduced survival times and increased mortality risks in all endpoints. Multivariable Cox models confirmed LAR as an independent predictor of 30- and 90-day mortality. RCS analysis indicated a linear relationship between LAR and ICU mortality (P = 0.109), and a non-linear association with hospital (P = 0.005), 30-day (P < 0.001), and 90-day mortality (P < 0.001). Subgroup analyses highlighted significant interactions for respiratory failure and GCS.Conclusion: LAR is a robust predictor of short- and long-term mortality in critically ill IS patients, offering clinicians a valuable tool for risk stratification and decision-making.
Keywords: lactate-to-albumin ratio; ischemic stroke; mortality; MIMIC-IV Database